Intention‐to‐treat survival benefit of liver transplantation in patients with hepatocellular cancer. Issue 6 (6th November 2017) - Lai, Quirino; Vitale, Alessandro; Iesari, Samuele; Finkenstedt, Armin; Mennini, Gianluca; Spoletini, Gabriele; Hoppe‐Lotichius, Maria; Vennarecci, Giovanni; Manzia, Tommaso M.; Nicolini, Daniele; Avolio, Alfonso W.; Frigo, Anna Chiara; et al.
Abstract : The debate about the best approach to select patients with hepatocellular cancer (HCC) waiting for liver transplantation (LT) is still ongoing. This study aims to identify the best variables allowing to discriminate between "high‐" and "low‐benefit" patients. To do so, the concept of intention‐to‐treat (ITT) survival benefit of LT has been created. Data of 2, 103 adult HCC patients consecutively enlisted during the period 1987‐2015 were analyzed. Three rigorous statistical steps were used in order to create the ITT survival benefit of LT: the development of an ITT LT and a non‐LT survival model, and the individual prediction of the ITT survival benefit of LT defined as the difference between the median ITT survival with (based on the first model) and without LT (based on the second model) calculated for each enrolled patient. Four variables (Model for End‐Stage Liver Disease, alpha‐fetoprotein, Milan‐Criteria status, and radiological response) displayed a high effect in terms of delta benefit. According to these risk factors, four benefit groups were identified. Patients with three to four factors ("no‐benefit group"; n = 405 of 2, 103; 19.2%) had no benefit of LT compared to alternative treatments. Conversely, patients without any risk factor ("large‐benefit group"; n = 108; 5.1%) yielded the highest benefit from LT reaching 60 months. Conclusion: The ITT transplant survival benefit presented here allows physicians to better select HCC patients waiting for LT. The obtained stratification may lead to an improved and more equitable method of organ allocation. Patients without benefit should be de‐listed, whereas patients with large benefit ratio should be prioritized for LT. (Hepatology 2017;66:1910–1919)